Complex Morphology of Subducted Lithosphere in the Mantle below the Molucca Collision Zone from Non-linear Seismic Tomography - Sri Widiyantoro (Institute for Research and Community Services, Institut Teknologi Bandung, 2003)
Results of seismic studies presented in previous publications depict two opposing subducted oceanic lithospheric slabs under the Molucca region. This unique structure is related to the arc-arc collision between the Halmahera and Sangihe arcs. Recently, we have revisited the complex subduction zone structure by employing a non-linear tomographic imaging technique in which 3-D ray tracing has been implemented. We have used P- as well as S-wave arrival times from carefully reprocessed global data set. The results provide some improvements in the positioning of wave-speed anomalies. Consistent with earlier results, the new P-wave model depicts the two opposing subducted slabs of the Molucca Sea plate. The intriguing new observation is that the westward dipping slab appears to penetrate into the lower mantle by taking the form of folded slab. We envisage that the folding behavior may have been caused by the shift of the whole subduction system in the Molucca region toward the Eurasian continent due to the westward thrust of the Pacific plate combined with the large left-lateral movement of the Sorong fault. The inversion of traveltime residuals of direct S phases strongly confirms the new observation.